Effect of curcumin on human colon cancer multidrug resistance in vitro and in vivo (Clinics, 2013)
OBJECTIVE: To determine whether curcumin reverses the multidrug resistance of human colon cancer cells in vitro and in vivo. METHODS: In a vincristine-resistant cell line of human colon cancer, the cell viability of curcumin-treated cells was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Rhodamine123 efflux was evaluated to detect P-glycoprotein transporter activity, and expression of the multidrug resistance protein 1 and survivin genes was analyzed by reverse transcription polymerase chain reaction and western blotting. In addition, xenograft mouse tumors were grown and treated with curcumin. The morphology of the xenografts was investigated by hematoxylin-eosin staining. The in vivo expression of the multidrug resistance gene and P-glycoprotein and survivin genes and proteins was observed using reverse transcription-polymerase chain reaction and western blotting, respectively. RESULTS: Curcumin was not obviously toxic to the vincristine-resistant human colon cancer cells at concentrations less than 25 μM, but the growth of cells was significantly inhibited. At concentrations greater than 25 μM, curcumin was toxic in a concentration-dependent manner. The sensitivity of cells to vincristine, cisplatin, fluorouracil, and hydroxycamptothecin was enhanced, intracellular Rhodamine123 accumulation was increased (p